Cicada nymphs dominate American black bear diet in a desert riparian area. Issue 3 (1st March 2022) - Lundgren, Erick J.; Moeller, Karla T.; Clyne, Michael Otis; Middleton, Owen S.; Mahoney, Sean M.; Kwapich, Christina L.
Abstract: American black bears are considered dependent on high‐elevation forests or other montane habitats in the drylands of western North America. Black bear sign, including that of cubs, was observed throughout the summers of 2015, 2016, and 2018 along a perennial desert river in the Sonoran Desert of Arizona. We analyzed the contents of 21 black bear scats, collected from May to October of 2016 and 2018. Apache cicada nymphs ( Diceroprocta apache ) were the dominant food item, occurring in 90% of scats and comprising an average of 59% of scat contents. In the process of excavating these nymphs, bears created large areas of turned‐over soil, a form of ecosystem engineering with potential implications for soils, vegetation, and fluvial geomorphology. Given that species distributions are shaped by physiological and ecological contexts, as well as anthropogenic legacies, it is possible that black bears once occurred more commonly in desert riparian systems prior to widespread agricultural development, hunting, and dewatering. Although more research is necessary, we suggest that desert riparian systems may be an alternative habitat for black bears. Better understanding the diet and habitat breadth of American black bears is important in the context of increasing landscape fragmentation and militarization in the U.S.‐Mexican borderlands. Abstract : American black bears are generally considered forest habitat dependent species. However, we report on black bears in a riparian system in the Sonoran Desert, with an unusual diet dominated by cicada nymphs. Our results suggest that much remains unknown about the ecologies of even a well‐studied species like American black bears.